2001
DOI: 10.1575/1912/3043
|View full text |Cite
|
Sign up to set email alerts
|

The aggregation of clay minerals and marine microalgal cells : physicochemical theory and implications for controlling harmful algal blooms

Abstract: In recent years, the use of clay minerals has emerged as one of the most promising strategies for directly controlling harmful algal blooms (HABs). Its principle is based on the mutual aggregation of algal cells and mineral particles, leading to the formation of large flocs that rapidly settle to the ocean floor. This work investigated the effectiveness of various domestic clays against a number of bloom-forming species from the United States. Twenty-five clays were tested against the dinoflagellate, Karenia b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
1
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(43 citation statements)
references
References 19 publications
1
40
1
1
Order By: Relevance
“…This indicates the release of intracellular toxins. Physical contact between clay particles and algal cells has previously been demonstrated to cause lysis in a range of harmful algal species, ranging from fragile raphidophytes to armored dinoflagellates [19][20][21][22]. Observed higher particle counts in the lower size range (<4 μm) that neither corresponded to P. parvum cells nor clay particles support this suggestion, as these smaller-sized particles likely represent cell fragments and/or aggregates of cell fragments and clay particles.…”
Section: Phoslock™ (B3) Applicationmentioning
confidence: 87%
See 1 more Smart Citation
“…This indicates the release of intracellular toxins. Physical contact between clay particles and algal cells has previously been demonstrated to cause lysis in a range of harmful algal species, ranging from fragile raphidophytes to armored dinoflagellates [19][20][21][22]. Observed higher particle counts in the lower size range (<4 μm) that neither corresponded to P. parvum cells nor clay particles support this suggestion, as these smaller-sized particles likely represent cell fragments and/or aggregates of cell fragments and clay particles.…”
Section: Phoslock™ (B3) Applicationmentioning
confidence: 87%
“…Later work, focusing on the clay-mediated removal of Karenia brevis dinoflagellate cells and Microcystis aeruginosa cyanobacterial toxins, reported evidence of direct adsorption of water-soluble, extracellular ichthyotoxins to bentonite-type clays [17,18]. This latter property of clay deserves special attention, since algal cell lysis in response to collisions with clay particles has previously been reported [19][20][21][22]; a process that could greatly amplify ichthyotoxic effects through the release of intracellular ichthyotoxins [23,24]. The potential of clays to adsorb P. parvum ichthyotoxins and the factors governing adsorption remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…These results indicated that cell mortality of M. aeruginosa occurred after flocculated by CMK. Physical contact between the algal cells and clays was proposed as the main reason for the death of algal cells since no cytotoxic substances was detected releasing from the clay (Sengco 2001). In the present study, we also tested the effect of chitosan and kaolinite separately on cell viability of M. aeruginosa NIES-843, and no of them could cause the lethal effect on the Microcystis cells as CMK loading at corresponding levels of 80 and 160 mg/l respectively (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…A few studies, towards cell viability and recovery possibility after flocculation, indicated that clay flocculation could cause cell mortality of some red tide forming algae (Shirota 1989;Bae et al 1998;Sengco 2001), but mechanism underlying cell mortality is not fully understood. The principle of clay flocculation is based on the mutual aggregation of algal cells with mineral particles, leading to the formation of large flocs that rapidly settle into the floor of water column.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation